Audit Digitalization: A Transformation In Big Data Management - Muslimin, Muh. Fahri; Purnamasari, Rini; Nur , Sri Wahyuni (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Governments and businesses around the world are currently undergoing an unprecedentedtransformation, particularly with the widespread adoption of digital technologies. Thistransformation has compelled organizations to redesign their business models, utilize digitaltools to enhance operational efficiency, capture new markets, and create innovations thatstrengthen competitiveness. In this context, digital transformation is not only changing howcompanies operate but also affecting the entire scope of work, including in the fields ofaccounting and auditing. Technologies such as Big Data, the Internet of Things (IoT), and CloudComputing have enabled accounting and auditing processes to become more efficient and haveassisted in managing complex data. Digitalization in auditing, in particular, provides ease inmanaging big data and enhances the reliability and efficiency of audits. However, thistransformation also brings challenges, especially in terms of the efficiency and effectiveness ofIT audit processes. This article explores the impact of digital transformation on the quality ofaudit work, the role of digitalization in big data management, and the process of implementingdigital audit. The findings of this study indicate that digital transformation presents newopportunities and challenges in auditing, requiring auditors to adjust and enhance theircompetencies.